Hong Kong veterinarians’ encounters with client-related stress – a qualitative study - Chan, Camille K. Y.; Wong, Paul W. C. (Frontiers in Veterinary Science, 2023)
Limited research has explored the stressors experienced by veterinarians in East Asia. Metropolitan cities like Hong Kong may have overlooked factors that significantly contribute to veterinarians' stress. This paper examines how client-related stressors and contextual factors contribute to the stress levels of Hong Kong-based veterinarians.Veterinarians from small domestic animal practices in Hong Kong were recruited using purposive and targeted snowball samplings until thematic saturation was achieved. Semi-structured in-depth interviews were conducted, audio-recorded, transcribed, coded, and analysed using reflexive thematic analysis with an interpretivist paradigm based on Heidegger's phenomenological approach.Eighteen participating veterinarians described the expectations of and communication with the animalhealth enthusiast (AHE) community, including clients, pet owners, and animal lovers, as their primary source of stress. Discrepant expectations and miscommunication between the AHE and veterinary communities, along with contextual factors such as convenience in clinic switching, negative online reviews, and the relatively short history of the veterinary profession history in the multilingual city, were identified as contributing factors to their stress. Recent socio-political events and the pandemic further intensified societal emotions, leading some clients to project frustrations onto perceived authority figures, including health professionals.The study highlights that client-related stress extends beyond the health of animal patients, encompassing the expectations of the AHE community, which requires professional-level communication skills to build a mutually respectful three-party relationship. Besides, Hong Kong's unique contextual and historical factors subtly but chronically impact veterinary practices that can be 2 easily overlooked. Recognising these influences and how they interact are crucial for collaboration within and beyond the profession, at the policy level to improve veterinary training and practices.Our findings highlight the importance of expectation management and improving communication quality to foster healthy relationships among animals, AHE community, and veterinary professionals. These efforts are believed to alleviate veterinarians' stress and enhance the well-being of all parties involved. We recommend incorporating effective communication and self-care discussions into the veterinary curriculum and advocating for ongoing training for practicing veterinarians. At the community level, encouraging open dialogues between animal caregivers and veterinary professionals can help address expectation discrepancies.